2009
DOI: 10.1186/bcr2348
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiling of male breast cancer

Abstract: Introduction MicroRNAs (miRNAs) are a class of small noncoding RNAs that control gene expression by targeting mRNAs and triggering either translation repression or RNA degradation. Their aberrant expression may be involved in human diseases, including cancer. To test the hypothesis that there is a specific miRNA expression signature which characterizes male breast cancers, we performed miRNA microarray analysis in a series of male breast cancers and compared them with cases of male gynecomastia and female brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 41 publications
6
87
0
Order By: Relevance
“…The identification of tumor-specific miRNAs and their target genes seems to be crucial to validate the molecular mechanism in tumorgenesis. has been reported to be involved in some malignant tumors [16,17]. Here, we demonstrated the relation of miR-191, NDST1, and MGC803 cell proliferation.…”
Section: Ndst1 Could Suppress Mgc803 Cell Proliferationmentioning
confidence: 66%
See 1 more Smart Citation
“…The identification of tumor-specific miRNAs and their target genes seems to be crucial to validate the molecular mechanism in tumorgenesis. has been reported to be involved in some malignant tumors [16,17]. Here, we demonstrated the relation of miR-191, NDST1, and MGC803 cell proliferation.…”
Section: Ndst1 Could Suppress Mgc803 Cell Proliferationmentioning
confidence: 66%
“…MiR-191 is found to be associated with some malignant tumors, such as ovarian cancer [16] and male breast cancer [17]. MiR-191 is also differentially expressed in T regulatory cells of Type 1 diabetic patients [18].…”
Section: Introductionmentioning
confidence: 99%
“…The need for more refined therapeutic treatments for male breast cancer (MBC) is evidenced by a steady stream of publications highlighting gender-specific differences using IHC (1-5), genetics (6)(7)(8)(9)(10)(11), and more recently, epigenetics (12)(13)(14)(15). Of note, although MBC is similar histologically to female breast cancer (FBC), with the same panel of biomarkers used to guide treatment and prognosis, more rigorous interrogation of the underlying genetics shows heterogeneity in MBC as recognized in FBC where molecular profiling has identified different subgroups that correlate with varying clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, while FBC has been intensively investigated by comprehensive molecular analysis, at present no gene expression data are available for male breast cancer. Recently, Fassan et al reported a set of microRNA as differentially expressed by comparison of 23 male and 10 female breast cancer samples [10].…”
Section: Introductionmentioning
confidence: 99%